2023
DOI: 10.3390/su151410832
|View full text |Cite
|
Sign up to set email alerts
|

MaaS Implications in the Smart City: A Multi-Stakeholder Approach

Abstract: Cities worldwide are calling for smart mobility strategies to tackle the negative externalities of their transport networks. Mobility as a Service (MaaS) is expected to introduce a new mobility model that promotes smarter and more sustainable urban futures. Given the novelty of the concept, this paper explores the implications that might arise from the implementation of MaaS in today’s metropolises in relation to the six dimensions of smart cities: smart governance, smart economy, smart mobility, smart environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 112 publications
(140 reference statements)
1
7
0
Order By: Relevance
“…Such collaborations may further new ways of working among various stakeholders and innovative uses of technology, which adds to knowledge on multi-stakeholder interactions and collaborative models for smart city development and governance frequently advocated for in the literature [7,9,[29][30][31][32][33][34][35][36]. In parallel, our case studies contribute to the emerging research indicating that community organizations such as public libraries can develop smart citizens [9,66,[83][84][85][86][87][88][89] and thus add to the studies on the roles of different actors in developing smart citizens [51,57,65,76,80,121,143,151].…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Such collaborations may further new ways of working among various stakeholders and innovative uses of technology, which adds to knowledge on multi-stakeholder interactions and collaborative models for smart city development and governance frequently advocated for in the literature [7,9,[29][30][31][32][33][34][35][36]. In parallel, our case studies contribute to the emerging research indicating that community organizations such as public libraries can develop smart citizens [9,66,[83][84][85][86][87][88][89] and thus add to the studies on the roles of different actors in developing smart citizens [51,57,65,76,80,121,143,151].…”
Section: Discussionsupporting
confidence: 52%
“…Early studies approach this topic from a social and human capital lens by discussing the term "smart people" as a significant dimension of smart cities and characterizing smart people as comprising "various factors like affinity to lifelong learning, social and ethnic plurality, flexibility, creativity, cosmopolitanism or open-mindedness, and participation in public life" [28,112,113]. Further, smart people use technology and data to make informed choices related to resource and service consumption towards greater sustainability and interact with others about public affairs [65,[102][103][104][105][106][107]. Smart people are also skilled individuals who contribute to socioeconomic development [33,45,79,[108][109][110][111], for example, as innovators [114] and problemsolvers for urban issues [1,8,78].…”
Section: Understanding Smart Citizensmentioning
confidence: 99%
See 2 more Smart Citations
“…A study [120] indicated that users' perceptions of information security are supported by providing robust security defense techniques such as multi-factor authentication, encryption, and validation. Another study [121] confirmed that the security of online services is considered the primary factor determining the success of smart cities. Therefore, we hypothesized that providing security procedures would increase the successful adoption of smart cities.…”
Section: • Information Securitymentioning
confidence: 87%